If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 12 = 8x + 4 Reorder the terms: 12 + 10x = 8x + 4 Reorder the terms: 12 + 10x = 4 + 8x Solving 12 + 10x = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 12 + 10x + -8x = 4 + 8x + -8x Combine like terms: 10x + -8x = 2x 12 + 2x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 12 + 2x = 4 + 0 12 + 2x = 4 Add '-12' to each side of the equation. 12 + -12 + 2x = 4 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 4 + -12 2x = 4 + -12 Combine like terms: 4 + -12 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 4x-7=3x-12 | | 5m+5.75=43.25 | | 8x-(600+2.50x)=1200 | | w-1/3=2 | | -x+5=x-11 | | 3b=20 | | 3x+1y=5 | | 8=2(w-2) | | -6u+7= | | 5+d=8d-7 | | 3/5c=2c-7 | | 9-q=5 | | 24/48=50/x | | x+y=10000 | | 12k-11k+2=16 | | 12-8(4-s)+3(s+3)=27 | | 3-2(x-5)=13 | | x(3+2)+9=2x-12 | | 8w+2w-2=18 | | 5c+12-3c=28 | | x-sqrt(40-3x)=0 | | 4x+5(3x-3)=6 | | 2m-4=10+18 | | x(x-3)(x+12)=324 | | 3x+6y=-9 | | 7x+4y=53500 | | 2m-4=10+16 | | F(t)=0.25t^2-0.5t+3.5 | | 26=-7x+5(x+8) | | c+4=3/4 | | 6x-(5x+4)=5x-32 | | -3t-8+7t=35+9t-2 |